Highly sensitive electrospun poly(HEMA-co-NMA)/BPDO nanofiber membranes for sensing metal ions in aqueous media - S. Chaudhuri; C. M. Wu; Y. C. Chiu; D. H. Kuo (eXPRESS Polymer Letters, 2021)
The study presents new on/off switchable nanofiber membranes with high sensitivity for detecting Co2+ and Cu2+ ions. The nanofiber membranes were fabricated by electrospinning (ES) the poly[(2-hydroxyethylmethacrylate-co-N-methylolacrylamide)] [poly(HEMA-co-NMA)] copolymer with different quantities of 2,2′-bipyridine-3,3′-diol (BPDO). Poly(HEMA-co-NMA)random copolymers with various molar ratios of the HEMA and NMA monomers were synthesized by free radical polymerization. The HEMA and NMA moieties were specifically selected to promote hydrophilicity and crosslinking reactions, which ultimately support a mechanically stable structure in aqueous media. ES nanofiber membranes S1-0.5, with a HEMA:NMA molar ratio of 77:23 and 0.5 wt% of BPDO showed strong photoluminescence quenching upon exposure to Co2+ and Cu2+ ions at concentrations ranging from 10–7 to 10–4 M. Moreover, the nanofiber membranes exhibited reversibile on/off fluorescence emission properties upon the sequential addition of Cu2+ ions and ethylenediaminetetraacetic acid (EDTA). These results demonstrate a simple fabrication strategy for nanofiber membranes that have the potential to be effective for the real-time sensing of metal ions.